Diversification and post-glacial range expansion of giant North American camel spiders in genus Eremocosta (Solifugae: Eremobatidae) - Carlos E. Santibáñez-López; Paula E. Cushing; Alexsis M. Powell; Matthew R. Graham (Scientific Reports, 2021)
Abstract Species of camel spiders in the family Eremobatidae are an important component of arthropod communities in arid ecosystems throughout North America. Recently, research demonstrated that the evolutionary history and biogeography of the family are poorly understood. Herein we explore the biogeographic history of this group of arachnids using genome-wide single nucleotide polymorphism (SNP) data, morphology, and distribution modelling to study the eremobatid genus Eremocosta, which contains exceptionally large species distributed throughout North American deserts. Relationships among sampled species were resolved with strong support and they appear to have diversified within distinct desert regions along an east-to-west progression beginning in the Chihuahuan Desert. The unexpected phylogenetic position of some samples suggests that the genus may contain additional, morphologically cryptic species. Geometric morphometric analyses reveal a largely conserved cheliceral morphology among Eremocosta spp. Phylogeographic analyses indicate that the distribution of E. titania was substantially reduced during the last glacial maximum and the species only recently colonized much of the Mojave Desert. Results from this study underscore the power of genome-wide data for unlocking the genetic potential of museum specimens, which is especially promising for organisms like camel spiders that are notoriously difficult to collect.